Remarks on the marketing of educational nowadays - CHIRIMBU, Sebastian; BARBU-CHIRIMBU, Adina; RAŞCU PISTOL, Silvia (Annals of Spiru Haret University. Economic Series, 2011)
This article examines the marketing of educational products and services based on theoretical premises of marketing as defined in the specialized literature; were also identified the main characteristics of the marketing process of the teacher-manager: knowledge, identification and initial evaluation of the students’ expectations and needs of training and information. In our daily work, marketing becomes an essential element of the teacher’s strategic management, influencing our decisions in the field of course design, organization, coordination and evaluation (of the academic courses).